Hydrology, vegetation, and climate change in the southern Everglades during the Holocene - Winkler, M. G.; Sanford, P. R.; Kaplan, S. W. (Bulletin of American Paleontology, 2001)
Paleoecological study of 18 AMS-dated sediment cores from the southern Everglades provides evidence of a shifting mosaic of biotic communities in the past similar to those on the Everglades landscape today. Our results also indicate initiation of Everglades peatlands at 5900 yr B. P., the importance of fire (from charcoal analysis) as a structuring agent in the tropical Everglades, evidence of past plant communities (Isoetes marshes) not present in the modern landscape, and the introduction of exotic plants (Schinus, Casuarina, etc.) today. Past vegetation changes are documented by pollen and sclereid changes. Past water level changes are documented by plant community changes, diatom species and habitat changes, sponge spicule changes, and by intervals of peat (wet) or marl (dry) deposition in the sediment cores. Marl deposition dominates today at these sites in the southern Everglades, a long-term trend exacerbated by human impacts. The Everglades may become less complex in the near future as introduced plants outcompete native vegetation and decreased water levels result in decreased peat production. A rewatering plan must include both wet and dry seasonal cycles in order to preserve the shifting mosaic nature of the landscape and to maintain the Everglades as a functional habitat for both plants and animals.
id: 125